Multiple retained deciduous and abnormally impacted permanent teeth in non-syndromic patient– A CBCT Presentation - Kamala, K. A.; S. Sankethguddad, S. Sankethguddad; SR, Ashwinirani; Mahajan, Madhura (Journal of Neonatal Surgery, 2025)
This case report presents a 21-year-old non-syndromic male patient with multiple impacted permanent teeth and retained deciduous teeth, a rare dental anomaly typically associated with syndromes or systemic conditions. The patient exhibited no systemic or familial anomalies, and his clinical presentation included missing teeth, retained primary teeth, and difficulties with mastication. Cone Beam Computed Tomography (CBCT) was utilized for detailed imaging, revealing various types of impactions including vertical, mesioangular, horizontal, and inverse, as well as rotated teeth. A multidisciplinary treatment plan was formulated involving extractions, root canal therapy, and comprehensive orthodontic management. The case emphasizes the value of CBCT in accurate diagnosis and treatment planning, particularly in non-syndromic cases where traditional radiographs may be insufficient. It also highlights the importance of early intervention, a collaborative approach, and ongoing research in understanding idiopathic cases of multiple impactions to achieve functional and aesthetic rehabilitation.